Level of Awareness Regarding COVID-19 Among Laborers, Maintenance and Sanitary workers - Himayat Ullah, Ghulam Mustafa, Muhammad Ashraf, Niaz Ali, Muhammad Shabbir, Yasser Salem Nasrallah, Shabir Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 is a global pandemic and the most serious health issue worldwide now a day. There is a lot of research going on regarding this issue. Many sectors of the community are focussed but some are still not properly approached like those with poor socioeconomic status, with high exposure to the community. This study was aimed at one of such group i.e., labourers, maintenance and sanitary workers. Methodology: It was a questionnaire-based cross-sectional study. The questionnaire contained multiple choice questions based on simple laymen knowledge regarding covid-19. The sampling technique was non-probability consecutive sampling. The sample size (169) and the questionnaire were filled in by the one health professional in face-to-face interview. Results: Total 169 participants, all males, were included in this study. The age range was 18-60 years (median 36 years). Most of the participants were sanitary workers (89.9%) with a major chunk from Bangladesh (82.8%) followed by India (15.4%). The level of awareness was considered good, average and poor with more than 20 (80%), 15 to 20 (58- 79%), and less than 15 (54%) correct replies, respectively. Only 35 participants (20.7%) ranked as good while 110(65.1%) had average and 24(14.2%) had poor knowledge. Conclusion: The level of awareness among labour class of the society is quite low. Educating them regarding COVID-19 is very important in order to control this pandemic.